Biodiversity and conservation assessment of freshwater fishes of Harsi Reservoir, Madhya Pradesh, India - Shrotriy Ved Prakash (International Journal of Life Sciences, 2015)
This contribution focuses on the diversity, population and conservation aspects of fishes in one of the large freshwater body of Madhya Pradesh, ‘Harsi reservoir’. The extensive survey was conducted from April, 2005 to March, 2007. A total of 51 species were recorded belonging to 33 genera, 16 families and 7 orders. As far as the fishes under different orders are concerned, order Cypriniformes consists of 15 genera belonging to 3 families, Siluriformes of 10 genera to 6 families, Perciformes of 3 genera to 3 families, Osteoglossiformes and Synbranchiformes of 2 genera each to singular family and Clupeiformes and Beloniformes of 1 genus each, to single family. The analysis showed that 07 and 04 fish species, as endangered by two different mode of classification. Apart from the Indian Major Carps, certain threatened species viz., Chitala chitala, Tor tor, Ompok bimaculatus and Eutropiichthys vacha were recorded from the reservoir. A sisorid, Gagata sexualis has been reported for the first time from this region. The study confirms that this freshwater body may prove congineal for conservation of regional fish diversity, especially for local and endangered fish species.